Efektivitas Sosialisasi terhadap Peningkatan Pengetahuan Penyuluh Pertanian tentang PermenpanRB 35/2020 di Kabupaten Bengkulu Selatan - Andi Ishak; Sidiq Budiyono; Sudamansyah; Fauzi Emlan; Firison Jhon; Kusnadi Harwi (Balai Pelatihan Pertanian Jambi, 2022)
Understanding of functional position regulations by agricultural extension agents is very important in carrying out duties and career advancement. The Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 35 of 2020 (PermenpanRB 35/2020) concerning Functional Positions of Agricultural Extension Agents is the newest regulation that has not been widely. This study aims to determine the effectiveness of socialization on the level of knowledge of agricultural extension agents in South Bengkulu Regency about the regulation. Data collection was carried out through a survey involving 15 agricultural extension agents in South Bengkulu Regency as respondents in December 2021. Data analysis used paired t-test. The results showed that the average level of knowledge of extension agents increased from 74.44 to 88.00 from a scale of 0-100 or an average increase of 13.56% due to socialization. This increase in knowledge is significant at the level of α=0.05, indicates that the socialization of PermenpanRB 35/2020 is effective in increasing the knowledge of extension agents in South Bengkulu Regency. Therefore, it is necessarry further socialization of PermenpanRB 35/2020 in the subdistrict level in order to increase the knowledge of agricultural extension agents about this rule.